The Recognition of Internal Decisions of Adoption and Cross-Border Family Mediation: Array - Ion, Carmen; Giurgea, Lenuta (Journal of Danubian Studies and Research, 2021)
We have chosen as our theme the recognition of internal decisions of adoption and cross-border family mediation convinced that the subject of its legal implications is far from being exhausted in the hope that we can make our contribution to the understanding of this complex legal institution. We have tried to explain both the elements of legislative continuity and discontinuity in the regulation of adoption. The research methodology also involved the deepening of Community and internal legislation on internal adoption decisions and cross-border family mediation. With all the limits of the law at the European level, there is no binding framework for the recognition of adoption decisions handed down following a national procedure, legislative action is needed to ensure that the right of European citizens to family life and freedom of movement is respected at all times. Advances in trade and technology have contributed to increased interaction between different countries, which has in fact led to an increase in the number of cross-border disputes. Unfortunately, cross-border disputes are often very complicated due to the involvement of various national laws, language barriers, cultural differences. The general conclusion is drawn from the research we have undertaken is that both EU and Council of Europe legislation and national legislation reflect the importance of family relations for the child.